Lectotypification and observations on the morphology, distribution and conservation status of Isoetes luetzelburgii (Isoetaceae) - Pereira, Jovani Bernardino De Souza; Silvestre, Leandro C.; Santiago, Augusto C.p. (Phytotaxa, 2018)
Isoetes is a worldwide aquatic plant group with ca. 250 species. In South America, Isoetes luetzelburgii is one of the few species that inhabits semi-arid areas. This is an endangered species known from only few collections, which causes uncertainty related to its morphological delimitation, distribution and conservation status. Efforts combining both field and herbarium investigations enabled us to identify several new populations in northern Brazil. In this study, we present a comprehensive assessment of the known distribution of I. luetzelburgii and provide a detailed description of the species. Because the holotype was never properly designated, we also provide the lectotypification for the name. The data presented here contribute to enhance our understanding of the taxonomy and natural history of this species. This understanding may also serve as a conservation tool for the protection of its populations.